Polymeric materials for controlled cellular adhesion and targeted delivery - Lui, Irene, author; McNaughton, Brian, advisor; Di Pietro, Santiago, committee member; Kennan, Alan, committee member (Colorado State University. Libraries, 2014)
Gaining control over cell adhesion and growth is a critical step in a variety of biomedical applications. Controlling the localization of cell adhesion and growth is typically achieved by coating a non-adhesive surface with adhesive small molecule or macromolecule reagents with affinity for a cell surface component. Cell-imprinting a hydrogel from a monolayer of cells transforms this material into a substrate for mammalian cell adhesion and growth. Cell-imprinted polyacrylamide hydrogels can be used as an inexpensive and simple substrate for directing cell adhesion and growth. Separately, as a result of a selection to identify a PC-3 prostate cancer cell-selective cell-penetrating peptide, a linear 12-amino acid peptide "Ypep" (NYTFGLKTSFNVQ-C) has been identified, whose cell penetration potency and selectivity profiles are tightly controlled by multivalency effects. Alanine scanning mutagenesis was used to assess the specific contribution each residue plays in cell uptake efficiency and cell selectivity. The best mutant exhibits ~19-fold better uptake efficiency and ~4-fold improved cell-selectivity for a human prostate cancer cell line.